Respuesta :

Answer:

-16

Step-by-step explanation:

−2(32)−

8

2

+6

=(−2)(9)−

8

2

+6

=−18−

8

2

+6

=−18−4+6

=−22+6

=−16

Answer: -16
First you must go with the order of PEMDAS. Since there are no () we can skip to exponents;
-2x3^2 - 8 / 2 + 6 can be rewritten as:
-2x9 - 8/2 + 6
Then we have multiplication and division. Since there are both operations in this problem, we must solve from left to write.:
-2x9 = -18 and 8/2 = 4
So we can rewrite the equation to:
-18 -4 + 6
Lastly we have subtraction and addition.
-18-4 = -22 so now it’s
-22 + 6 = -16